Igor Shamo. Postlude - Lazarevska, July (Ukraine, 2014)
Cinema has the magical power to recreate time and places, to bring characters back to life. The hero of our film is composer Igor Shamo. Events unfold in Kyiv in the 50's and 80's. No films were made about him, only a few chronicles survived along with the family photo archive. Still the music continues.
Black and White
Verzio Film Festival Submission
Keywords: Documentary films